The structure of calcareous rings in Stichopus hermanni Semper and Holothuria atra Jaeger - Hawa Ismail; NG S.K; Hing H.L; Normalawati Shamsudin; Ridzwan Bin Hashim (penerbit ukm, 2004)
The calcareous rings of two species of local sea cucumbers, Stichopus hermanni Semper and Holothuria atra Jaeger, were located, dissected, exposed and recorded. The calcareous rings of both species each composed of ten plates knit together by connective tissues. The radial plate of H. atra was a square with a notch at the anterior part whereas in S. hermanni it was squarish consisting of 4 ridges in the anterior part with a notch at the posterior part. The interradial plates of both species were smaller than the radial plates. A ridge was present at the anterior part of the interradial plate in H. atra. In S. hermanii, the ridge at the anterior part of the interradial was thin and prominent. Under the scanning electron microscope the calcareous rings from the two species exhibited a mosaic of small, numerous spicules bound to each other.